Discovery of MYH14 as an important and unique deafness gene causing prelingually severe autosomal dominant nonsyndromic hearing loss. (April 2017) - Kim, Bong Jik; Kim, Ah Reum; Han, Jin Hee; Lee, Chung; Oh, Doo Yi; Choi, Byung Yoon
Abstract: Background: Pathogenic variants of MYH14 are known to be associated (in either a syndromic or nonsyndromic manner) with hearing loss. Interestingly, all reported cases to date of MYH14 ‐related nonsyndromic hearing loss with detailed phenotypes have demonstrated mild‐to‐moderate progressive hearing loss with postlingual onset. Methods: In the present study, targeted resequencing (TRS) of known deafness genes was performed to identify the causative variant in two multiplex families segregating autosomal dominant (AD) inherited hearing loss. Results: TRS uncovered two novel variants of MYH14 (c.A572G: p.Asp191Gly in the myosin head domain and c.C73T:p.Gln25* in exon 2) from two multiplex deafness Korean families. Notably, both probands showed phenotypes of congenital or prelingual severe hearing loss. It is remarkably uncommon to encounter such a severe‐to‐profound, prelingual, AD hearing loss. Given that the first variant, p. Asp191Gly, was the first documented missense allele discovered in the myosin head domain of this gene related to either congenital or prelingual severe nonsyndromic hearing loss, and also that the second variant, p. Gln25*, lead to a null allele, more severe phenotypes from our probands may have been the result of either genotype–phenotype correlation or genetic backgrounds, or both. Conclusions: In the present study, we report that MYH14 can manifest as nonsyndromic prelingual severe sensorineural hearing loss in an AD fashion in Koreans. The results of the present study suggest that further genetic studies of similar patients should consider MYH14 as a causative gene, and cochlear implantation during infant or early childhood should be indicated for those patients with certain MYH14 pathogenic variants.